Stratégies de légitimation et construction de l’autorité dans les discours vaccino-sceptiques et complotistes aux États-Unis. La mise en saillance comme outil de maximisation de l’adhésion de l’interlocuteur - Damien Lenoir (Anglophonia)
This article seeks to show how some syntactical, grammatical or lexical salience strategies work to enable the speaker, in vaccine-hesitant or conspiracy theory contexts, to legitimize their discourses and strengthen their authority as a reliable speaker in order to maximize the audience’s agreement with the theory. We define salience as the result of focusing strategies which do not rely on notions of information packaging, but on the selection of an interlocutive relation that can be disruptive, polemical, or consensual, and which enable the construction of a prevailing point of view. In this regard, such strategies are used for their cognitive effects on the audience, which, for example, allow for the topicalisation and focusing of a presupposed or shared knowledge, or for their argumentative advantage, as they allow for the restriction of meaning and the imposition of the speaker’s interpretation of reality, or for the emphasis on the viewpoint’s validity, significance or reliability.